Recombinant Nepenthesin II for Hydrogen/Deuterium Exchange Mass Spectrometry - Yang, Menglin; Hoeppner, Morgan; Rey, Martial; Kadek, Alan; Man, Petr; Schriemer, David C (Analytical chemistry, 2015)
The pitcher secretions of the Nepenthes genus of carnivorous plants contain a proteolytic activity that is very useful for hydrogen/deuterium exchange mass spectrometry (HX-MS). Our efforts to reconstitute pitcher fluid activity using recombinant nepenthesin I (one of two known aspartic proteases in the fluid) revealed a partial cleavage profile and reduced enzymatic stability in certain HX-MS applications. We produced and characterized recombinant nepenthesin II to determine if it complemented nepenthesin I in HX-MS applications. Nepenthesin II shares many properties with nepenthesin I, such as fast digestion at reduced temperature and pH, and broad cleavage specificity, but in addition, it cleaves C-terminal to tryptophan. Neither enzyme reproduces the C-terminal proline cleavage we observed in the natural extract. Nepenthesin II is considerably more resistant to chemical denaturants and reducing agents than nepenthesin I, and it possesses a stability profile that is similar to that of pepsin. Higher stability combined with the slightly broader cleavage specificity makes nepenthesin II a useful alternative to pepsin and a more complete replacement for pitcher fluid in HX-MS applications.
Keywords: deuterium; rekombinantní proteiny; vodík-deuteriová výměna; Deuterium Exchange Measurement; Mass Spectrometry; Deuterium; hmotnostní spektrometrie; Recombinant Proteins